Rancang Bangun Sistem Penguncian Pintu Menggunakan Rfid Berbasis Mikrokontroler Atmega 2560 - Mohammad Musa Ibrohim; Karya Suhada (Jurnal Interkom: Jurnal Publikasi Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2019)
Theft is a crime in Article 362 of the Criminal Code (Criminal Code), theft of many ways is one of gouging the door, destroying the building, forcing the victim to end with murder. The security guard did his best to secure a territory in order to avoid crime, one of which was theft. His ordinary theft occurs at a time when residents or owners are in a state of careless. Theft can happen anytime and anywhere, within a year of theft can reach dozens of times. To avoid this, the residents do security with a crude, at least the residents do the locking with a conventional lock on the door of the house, warehouse or room that there are precious objects. With the development of today's technology world, technological developments are also very rapid. One of the technological developments emerged Microcontroller, RFID, and other sensors. A microcontroller is a board used to control the input output of a circuit. Microcontrollers can be incorporated with RFID to be a door locking circuit, and can be added again with other sensors to get the maximum.